Developing Long Term Low Emissions and Climate Resilient Agricultural Development Pathways for Kenya: Setting priorities for national and subnational agriculture development - African Group of Negotiators Expert Support; Food and Agriculture Organization of the United Nations; Accelerating Impacts of CGIAR Climate Research for Africa (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Kenya has developed a long term low emission and climate resilient agriculture development pathways (Agriculture LTS). The Agriculture LTS provides the enabling framework to identify medium- and long-term agricultural strategies and actions at national levels and sub-national levels in a changing climate. It also provides a guide on climate smart investments that will enhance agricultural productivity, ensure food security, and deliver the country’s growth in agriculture.